Abuse of Power in Nancy Farmer's The House of the Scorpion (2002) - Vira Nabila Nursidik; Ali Mustofa (Tell : Teaching of English Language and Literature Journal, 2021)
This study aims to reveal abuse of power depicted in Nancy Farmer’s The House of the Scorpion using Daniel Sankowsky’s definition and characteristics of abuse of power by leader, Bob Jessop’s Marxist Approaches to Power, and Nicos Poulantzas’s destruction of the state. El Patrón as the leader of a country named Opium, abuse his power in Marxist way, which leads to destruction of the state. The analysis focuses on how abuse of power done by El Patrón and destruction of the state as the consequence. Throughout the analysis, El Patrón’s abuse of power is done by him as a leader through economic, political, and ideological class domination. Destruction of the state as the consequence of his abuse of power include the destruction of the Church and the family.